ABOUT BACKGROUND OF OCCURRENCE OF ERRORS IN THE TIME OF THE SCIENTIFIC-LINGUISTIC EXPERT EXAMINATION - Baikarimova , Нұргүл Айтмұханқызы; Shyngysbayeva , Дүйсенкүл Мұхамбетжанқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
The authors on the basis of expert examination of drafts of legal acts and international treaties by the Center of Linguistics of the Institute of Legislation highlights most often encountered deficiencies in the process of scientific and linguistic expertise. The authors cite the example the piece of their scientific and linguistic examination of the Draft Code of Administrative Procedures of the Republic of Kazakhstan and the Code of Civil Procedure. Analyzing the two texts in Kazakh and Russian the authors give their arguments concerning the usage of the word "подведомственность” (jurisdiction) in both language versions. In the opinion of the authors, in the semantic study, one nuance is very important - the meanings of words and expressions that are given in encyclopedic publications should not be considered separately from the real situation. Therefore, the expert should be fully aware of the events and the situation described in the text of the Draft Law. It is important that the expert of the Linguistics Center should bear in mind that the examination is conducted in the legal sphere, and this also requires a special approach, i.e. it demands compliance with legal techniques. In addition, it is noted that the Center for Linguistics should make careful choice of words in the Glossary of legislation terms. The authors complain that, along with the approved Rules for conducting scientific expertise on international treaties, the Republic of Kazakhstan intends to become a party to, as well as on draft international treaties (Resolution of the Government of the Republic of Kazakhstan dated September 14, 2010 No. 938), the Rules for conducting scientific expertise on draft regulations Government of the Republic of Kazakhstan dated August 31, 2016 No. 497), which are of a generalized nature, there are no approved Methodological recommendations for conducting scientific linguistic expertise in terms of the authenticity of the texts of draft laws in the Kazakh and Russian languages. Summarizing the article, the authors reflecting on the need to develop and approve a mechanism for conducting scientific linguistic expertise regarding the authenticity of texts of draft laws in the Kazakh and Russian languages at the level of the Government of the Republic of Kazakhstan in order to eliminate the prerequisites for the occurrence of flaws during scientific linguistic expertise.